Investigation of the Field and Temperature Dependences of the Resistance of Nanocarbons Modified by Nickel and Cobalt - T.A. Len; I.V. Ovsienko; L.Yu. Matzui; V. Ya. Tkachuk (Журнал нано- та електронної фізики)
The work is devoted to the study of the effect of modifying by magnetic metals of structurally different nanocarbon structures on their electrical and magnetotransport properties. The experimental temperature and field dependences of the resistivity in a wide temperature and magnetic field ranges are considered, and the analysis of their features and formation mechanisms is performed. Modification of nanocarbon by magnetic metals of the concentration of 10 wt. % almost does not influence the value and behavior of the temperature dependence of the resistivity of modified nanocarbon. The temperature dependence of the resistivity of modified nanocarbon is determined by the same mechanisms as for the initial (before modification) nanocarbon. We have revealed the difference in the effect of modifying by magnetic metals on the magnetotransport properties of different types of nanocarbon associated with the features of interaction of the magnetic metal particles with particles of nanographite and CNT.